Fractal micro- and nanodendrites of silver, copper and their compounds for photocatalytic water splitting - Sidorov, A.I.; Bezrukov, P.A.; Nashchekin, A.V.; Nikonorov, N.V. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2024)
The results of investigation of morphology and photocatalytic properties of thin films in a form of dendrites of silver and copper, and their compounds synthesized by the reaction of substitution, are presented. The morphology and the composition of the synthesized layers were performed by scanning electron microscope. It was shown that already through 2–3 s after the reaction beginning metal nanoporous layers up to 1 μm thick are formed on the substrates. Silver layers consist of micro-crystalline hexagonal plates and micro- and nano-dendrites. As the duration of the reaction increases the layers become more compacted, and the minimum of the pores size becomes 20 nm. In the case of the reaction with the copper salt the formation of copper microdendrites takes place immediately. The internal quantum yield of photocatalysis of water for silver and copper layers as well as for metal-semiconductor layers is 0.4–0.45 %. The obtained results can be used for the creation of photocathodes with large surface for photocathalytic water splitting in order to obtain hydrogen fuel.